Rapid Alterations in Cerebral White Matter Lipid Profiles After Ischemic-Reperfusion Brain Injury in Fetal Sheep as Demonstrated by MALDI-Mass Spectrometry. (July 2019) - Gallucci, Gina M; Tong, Ming; Chen, Xiaodi; Stonestreet, Barbara S; Lin, Amy; de la Monte, Suzanne M
Background: Perinatal ischemia-reperfusion (I/R) injury of cerebral white matter causes long-term cognitive and motor disabilities in children. I/R damages or kills highly metabolic immature oligodendroglia via oxidative stress, excitotoxicity, inflammation, and mitochondrial dysfunction, impairing their capacity to generate and maintain mature myelin. However, the consequences of I/R on myelin lipid composition have not been characterized. Objective: This study utilized matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) to assess alterations in cerebral supraventricular white matter myelin lipid profiles in a fetal sheep model of perinatal I/R. Methods: Fetal sheep (127 days gestation) were studied after 30 minutes of bilateral carotid artery occlusion followed by 4 (n = 5), 24 (n = 7), 48 (n = 3), or 72 (n = 5) hours of reperfusion, or sham treatment (n = 5). White matter lipids were analyzed by negative ion mode MALDI-MS. Results: Striking I/R-associated shifts in phospholipid and sphingolipid expression occurred over the 72-hour time course with most responses detected within 4 hours of reperfusion and progressing at the 48- and 72-hour points. I/R decreased expression of phosphatidic acid and phosphatidylethanol amine and increased phosphatidylinositol, sulfatide, and lactosylceramide. Conclusions: Cerebral I/R in mid-gestation fetal sheep causes rapid shifts in white matter myelin lipid composition that may reflect injury, proliferation, or recovery of immature oligodendroglia.